PROPOLIS SEBAGAI SUPLEMEN BAGI PENDERITA TUBERKULOSIS DEWASA - Pranandaru, Herlambang; Sembodo, Adi; Choirina, Julia; Wijaya, Fahrizal Kusuma; Sewaka, Septian Wisnu (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
One of current world health problems is tuberculosis. Propolis can inhibit M. tuberculosis growth and increase the mediator of macrophage activator. The aim to proof that propolis as a supplement to heal in tuberculosis.Â Research design is control experimental group, using 15 samples patient of positive BTA, divided into 2 groups, control (standard anti-tuberculosis) and experiment (combination of standard anti-tuberculosis+propolis). All patients randomly, take the propolis or placebo with 4 drops dosage every day during 2 month and BTA will be checked. The examination result shows that experiment group has better recovery than control group (p=0,020). It concluded that propolis can be a good choice as a supplement of treating infections caused by M.tuberculosis.Keywords: Propolis, Supplement, Recovery, Adult patient of tuberculosis.